Measurement and research methods in international marketing - Sarstedt, Marko; Schwaiger, Manfred, 1963-; Taylor, Charles R., 1961- (Advances in international marketing ;, 2011)
Publishing cross-national research is often a difficult endeavour as ensuring equivalence of method and measures can be challenging. Even though the importance of sound data and valid measures has long been an acknowledged, it is often problematic to follow required quality standards in concrete research situations. Against this background, this volume addresses issues pertaining measurement and research methodology in an international marketing context. Written by a group of internationally renowned scholars, the papers address a broad range of subjects including response-bias in cross-cultural research, problems with cultural distance measures, and construct specification. Others focus on the development and application of novel research methods, for example in the context of marketing efficiency measurement or international market segmentation. Collectively, the papers in this volume substantially further marketing knowledge and provide fruitful avenues for future research. As such, this volume is an invaluable asset to researchers, students and practitioners in this particular field.